Constructing an ideological profile as a method of researching political discourse - Filipczak-Białkowska, Anita (Methods of communication and media researches. Theoretical and analytical perspective, 2021)
The chapter describes the author's method of analyzing ideological discourse on the example of political discourse. The purposes for which it is intended require taking into account the fact that there is a common research area of ​​linguistics and political science. Starting from a systematic analysis of linguistic means (carried out in accordance with the assumptions of communicative grammar), the data obtained in this way is combined with the relevant aspects of ideological constructs. As a result of this operation, an ideological profile is created, precisely characterizing the views of the examined subject (person, group, institution). The method can be used to study extensive material databases as well as individual messages showing an ideological load, allowing for a clear presentation of results in the form of tables and graphs.